2021
DOI: 10.3390/jcm10050957
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplantation for Pleuroparenchymal Fibroelastosis

Abstract: Pleuroparenchymal fibroelastosis (PPFE), a new disease entity associated with interstitial pneumonia, is characterized by fibrosis and elastosis involving the pleura and subpleural lung parenchyma, predominantly in the upper lobe. As the awareness of this disease entity has increased, many studies have revealed the prevalence and incidence, clinical and pathological characteristics, and disease course of PPFE. Patients with PPFE reportedly have several unique clinical characteristics—including an extremely low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, the survival of patients with radiological PPFE waiting for LT was reported to be non‐inferior to that of patients with fibrotic ILDs without radiological PPFE 17 or those with other IIPs 34 . Recently, a few reports have shown the overall survival and physical outcome of patients with PPFE after LT 35–37 . Our study revealed acceptable post‐LT survival in patients with advanced PPFE, suggesting the suitability of LT for them (both patients with idiopathic disease and patients with secondary disease).…”
Section: Discussionmentioning
confidence: 53%
“…However, the survival of patients with radiological PPFE waiting for LT was reported to be non‐inferior to that of patients with fibrotic ILDs without radiological PPFE 17 or those with other IIPs 34 . Recently, a few reports have shown the overall survival and physical outcome of patients with PPFE after LT 35–37 . Our study revealed acceptable post‐LT survival in patients with advanced PPFE, suggesting the suitability of LT for them (both patients with idiopathic disease and patients with secondary disease).…”
Section: Discussionmentioning
confidence: 53%
“…Pneumothorax is one of the most common complications in idiopathic and non-idiopathic PPFE. PPFE patients have a higher incidence of pneumothorax than other IIPs [5]. The latency period of PPFE during which patients have no symptoms can be long, and abnormalities would only be noticed in radiological investigations.…”
Section: Discussionmentioning
confidence: 97%
“…In 2013, PPFE was recognized as one of the two most rare idiopathic interstitial pneumonias (IIPs) along with idiopathic lymphoid interstitial pneumonia [ 4 ]. PPFE comprises 5.8% to 10.4% of idiopathic pulmonary fibrosis (IPF) cases [ 5 ]. Oda et al found that 11 of 110 patients (10%) diagnosed with IPF had radiological PPFE while nine (8.2%) had the histological features of PPFE [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung transplantation is considered the only definitive therapy, but must be considered carefully given the significant pleural involvement that can produce surgical challenges. 7…”
Section: Clinical Discussionmentioning
confidence: 99%